IMPACT OF WATCHING ENGLISH MOVIES, SERIES, AND CARTOONS ON ENGLISH LANGUAGE LEARNING OF A PRIVATE UNIVERSITY IN BANGLADESH - Mahbub, Rahman M (Innovare Journal of Social Sciences, 2024)
The article examines the influence of English movies, series, and cartoons on students majoring in English at a university in Bangladesh. The objective of this study was to ascertain the potential impact of films, series, and cartoons on the acquisition of the English language and to determine the extent of their influence. This quantitative research centered on the English department located in Dhaka, Bangladesh. A set of questionnaires was employed to administer a series of inquiries to 140 students. The research uses both primary and secondary data sources. Primary data sources include surveys and interviews, while secondary data sources encompass journals, publications, previous research, and websites. This study has shown the significant impact exerted by English films, series, and cartoons on EFL learners. The development of English language proficiency – reading, speaking, listening, writing – was noticeably improved. It is found that watching English series, cartoons, and movies is a quick and effective way for EFL students to pick up the language. The approach functions as an audiolingual method, incorporating visual aids and facilitating situational language instruction. Moreover, the subtitles have been found to enhance both reading and writing abilities, as well as promote social interactions and foster a deeper understanding of the culture of native speakers. This research will also provide valuable insights for future scholars and researchers.